2020
DOI: 10.1002/ep.13541
|View full text |Cite
|
Sign up to set email alerts
|

Copper and lanthanum mixed oxides as catalysts for ethanol Guerbet coupling: The role of La3+ on the production of long‐chain alcohols

Abstract: Mixed oxides derived from the calcination of modified hydrotalcites precursors with copper and lanthanum were synthetized by the co‐precipitation method and characterized and applied as catalysts for ethanol Guerbet coupling reactions. The oxides obtained were used to convert ethanol into 1‐butanol and long‐chain alcohols, mostly 1‐hexanol. The selectivity for 1‐butanol and 1‐hexanol reached 62% and 10% for Cu‐MgAl(O) at 280°C. The addition of 1 mol% of La3+ (CuLa‐MgAl(O)) increased the number of basic sites c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Recently, many works have demonstrated the Guerbet reaction of bioethanol to butanol as fuel additives. Rechi Siqueira and co-workers reported a Cu-based catalyst derived from a hydrotalcite precursor for upgrading ethanol to butanol, which gave an ethanol conversion of ∼80% and butanol selectivity of 32% . Wang et al reported that CaC 2 exhibited a superior catalytic activity with a 1-butanol yield of 24.5 C-mol% in C–C coupling of ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many works have demonstrated the Guerbet reaction of bioethanol to butanol as fuel additives. Rechi Siqueira and co-workers reported a Cu-based catalyst derived from a hydrotalcite precursor for upgrading ethanol to butanol, which gave an ethanol conversion of ∼80% and butanol selectivity of 32% . Wang et al reported that CaC 2 exhibited a superior catalytic activity with a 1-butanol yield of 24.5 C-mol% in C–C coupling of ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the same authors used a Mg–Al–Ce hydrotalcites with Mg/(Al + Ce) = 2 and obtained a slightly higher butanol selectivity (68%) ( Larina et al, 2021 ). Perrone et al (2021) used a Cu–MgAl (O) catalyst at 280°C, obtaining a selectivity to butanol and hexanol of 62 and 10%, respectively. The addition of La (CuLa–MgAl (O)) increased the number of basic sites compared to that of Cu–MgAl (O), which changed the selectivity to butanol (16.7%) and 1-hexanol (41.7%) at 280°C.…”
Section: Introductionmentioning
confidence: 99%